Design estrutural baseado em desempenho aplicado ao desenvolvimento de estrutura de torre eólica - Marina Ferreira Borges (2015)
This work proposes to study the process of parametric and algorithm design integrating analysis and structural design for the generation of complex geometry structures. This methodology is based on Performative Model where the shape is generated using a performance criteria. In the approach the development of complex structures is only possible with the reversal process thinking to generate the form, where was established parameters as geometry, material and loading aspects. In this methodology, the shape is the result of a collaborative work between architects and engineers. Thus, the participation of the structural engineer is no longer only in the evaluation phase and appears in the early stages, creating a process of exploration and production of common knowledge among architects and engineers. To research performance-based design, it is proposed the development of a conceptual lattice wind tower. Thus, a system will be made to generate geometries using Rhinoceros software, the plugin Grasshoper, and programming language VB integrated with stress analysis through the plugin Scan & Solve. The form of the structure will be chosen aiming to combine aesthetics with structural optimization.